Performance Comparison of Cooling Tower Filler Used in the Induced Counter Flow Type Cooling Tower System - Wibisono, Yusuf (Fakultas Teknologi Pertanian Universitas Brawijaya, 2005)
Appropriate postharvest handling of agricultural products is important to maintain the quality. The objectives of the research were to design and to evaluate the performance of cooling tower system, and to compare the characteristics of cooling tower filler i.e. sponge stone and foam rubber sponge, respectively. The induced counter flow type cooling tower was used in this experiment, equipped with a 90 cm height tank made up of fibber glass. Each filler, either arranged in single or multi-layers, was in direct contact with the water and air used as a media in the cooling process. The results showed that the highest range was achieved by the use of a 5 layers foam rubber sponges i.e. 3.2°C at an L/G Ratio of 2.567, maximum cooling power of 2690.6 W and COP 12.9, at temperatures of 26.1°C (dry bulb) and 24.4°C (ambient),and ambient RH of 87%. The dry bulb and wet bulb of the air inlet temperature were 25.5°C and 24.3°C, respectively, while the respective water inlet and outlet temperature 27.4°C and 24.2°C, at L/G ratio of 0.91-2.33 kJ/kg.°C. Key words: induced counter flow, cooling tower, filler, range, L/G ratio